Climate and land use changes explain variation in the A horizon and soil thickness in the United States - Zhang, Yakun; Hartemink, Alfred E.; Vanwalleghem, Tom; Bonfatti, Benito Roberto; Moen, Steven (Communications earth & environment, 2024)
Understanding spatio-temporal changes in soil thickness and their natural and anthropogenic driving factors are essential for earth system modeling and natural resource conservation. It remains challenging to accurately quantify the spatial pattern of soil thickness, and there is no assessment of its temporal changes at the national scale across eco-climatic zones. Here we compiled a long-term (1950–2018), large-scale (conterminous United States of America) topsoil (A horizon, n = 37,712) and solum (22,409) thickness data to quantify their spatial and temporal variations using generalized additive models and selected chronosequences in land resource regions. Climate was found associated with the spatial distribution of soil thickness, and land use and erosion associated with its temporal variation. The A horizon and solum thickness displayed strong longitudinal patterns, correlated with soil moisture and temperature, respectively. Temporal changes in the thickness varied across land resource regions, affected by topography, land use, and erosion. Severe A horizon loss primarily occurred in Mollisols of the Central Great Plains, Alfisols on steep slopes, and soils under cropping. These findings enhanced our fundamental understanding of soil formation and biogeochemical cycles during the Anthropocene across scales and identified regions for conservation practices to reduce further topsoil loss.